Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s10620-020-06516-8
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Hsa_circ_0001017 Inhibited Gastric Cancer Progression via Acting as a Sponge of miR-197

Abstract: Background Gastric cancer (GC) is one of the most common digestive system diseases and yet lacks effective therapeutic regimen. Aims The aim of our present research was to probe the value of hsa_circ_0001017 in GC treatment. Methods qRT-PCR and Western blot were performed to detect gene and protein expressions, respectively. CCK-8 assay and clone formation assay were used to ensure the proliferation of GC cell lines. Transwell assay was performed to measure the migration and invasion of GC cell lines. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…NSC12618, a highly active anticancer compound, enhanced RhoB expression via c-Jun N-terminal kinase signaling and caused death in gastric carcinoma NUGC-3 cells [ 30 ]. Li et al suggested that by targeting the miR-197/RhoB signaling pathway, the circRNA Hsa_circ_0001017 suppressed GC cell proliferation, movement, and infiltration [ 31 ]. KR28 (1-allyl-4-dodecanoyl-1-ethyl-piperazin-1-ium; bromide), a new anticancer drug, promoted apoptosis by upregulating c-Abl and activating p38 MAPK/ATF-2 in response to ROS-mediated RhoB production [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…NSC12618, a highly active anticancer compound, enhanced RhoB expression via c-Jun N-terminal kinase signaling and caused death in gastric carcinoma NUGC-3 cells [ 30 ]. Li et al suggested that by targeting the miR-197/RhoB signaling pathway, the circRNA Hsa_circ_0001017 suppressed GC cell proliferation, movement, and infiltration [ 31 ]. KR28 (1-allyl-4-dodecanoyl-1-ethyl-piperazin-1-ium; bromide), a new anticancer drug, promoted apoptosis by upregulating c-Abl and activating p38 MAPK/ATF-2 in response to ROS-mediated RhoB production [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As our best knowledge, hsa_circ_0005035 was notably lower in lung cancer tissues and lung cancer cell lines than in the adjacent normal tissues and cells [ 17 ]. Hsa_circ_0001017 expression was decreased in glioma [ 18 ] and gastric cancer [ 19 ] tissues and cells. The opposite expression levels of hsa_circ_0001017 and hsa_circ_0005035 might be ascribed to different tumor backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that circ_0001017 might be an oncogene in the development of OS. Although the oncogenic role of circ_0001017 has not been reported yet, circ_0001017 as a tumor suppressor has been demonstrated as follows: Upregulation of hsa_circ_0001017 could notably muffle the proliferation as well as the metastasis of gastric cancer (GC) cell lines and impede the formation of GC tumor [ 19 ]. Overexpression of hsa_circ_0001017 inhibited glioma cell proliferation, migration and invasion and promoted glioma cell apoptosis, while the knockdown of hsa_circ_0001017 caused the opposite results [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their highly stable structural makeup, circRNAs can be readily detected in patient serum samples and in harvested exosomes, making them promising diagnostic targets. Indeed, prior studies have highlighted the value of circRNA-based diagnostic analyses in breast [ 7 , 8 ], colorectal [ 9 , 10 ], liver [ 11 , 12 ], gastric [ 13 , 14 ], and non-small cell lung cancer [ 15 , 16 ]. Functionally, these circRNAs can regulate diverse oncogenic activities such as the migration, proliferation, and survival of tumor cells.…”
Section: Introductionmentioning
confidence: 99%